A economia portuguesa no tempo de napoleão – constantes e linhas de força : António Alves Caetano. Lisboa: Tribuna Da História, [2008], 271, [1] P., IL., Bib., ISBN 978-972-8799-79-3 - Rangel, Danny (CEM – Cultura, Espaço & Memória, 2018)
.